Evaluation of the Root and Canal Morphology of Maxillary Permanent Molars and the Incidence of the Second Mesiobuccal Root Canal in Greek Population Using Cone-beam Computed Tomography - Nikoloudaki, Georgia E. (Open Dent J, 2015)
Objectives: Cone-Beam Computed Tomography is an alternative imaging technique which has been recently introduced in the field of Oral & Maxillofacial Radiology. It has rapidly gained great popularity among clinicians due to its ability to detect lesions and defects of the orofacial region and provide three-dimensional information about them. In the field of Endodontics, CBCT can be a useful tool to reveal tooth morphology irregularities, additional root canals and vertical root fractures. The objective of this study is to evaluate the root and root canal morphology of the maxillary permanent molars in Greek population using Cone-Beam Computed Tomography. Materials and Methods : 273 cone-beam computed tomography (CBCT) images were examined. The number of roots and root canals of the first and second maxillary molars were evaluated. Root canal configuration was classified according to Weine’s classification by two independent examiners and statistical analysis was performed. Results : A total of 812 molars (410 first and 402 second ones) were evaluated. The vast majority of both first and second molars had three roots (89.26% and 85.07%, respectively). Most first molars had four canals, while most second molars had three. In the mesiobuccal roots, one foramen was recorded in 80.91% of all teeth. Other rare morphologic variations were also found, such as fusion of a maxillary second molar with a supernumerary tooth. Conclusion : Within the limitations of this study, it can be concluded that more attention should be given to the detection of additional canals during root canal treatment in maxillary permanent molars. Towards this effort, CBCT can provide the clinician with supplemental information about the different root canal configurations for successful Root Canal Treatment.